Epitaxial Cobalt Oxide Films with Wurtzite Structure on Au(111). Issue 11 (1st October 2021) - Ammon, Maximilian; Baumann, Sara; Kißlinger, Tilman; Rieger, Janek; Fauster, Thomas; Redinger, Josef; Hammer, Lutz; Schneider, M. Alexander
Abstract : Several‐nanometer‐thick, closed, and epitaxial cobalt(II) oxide films with wurtzite crystal structure (w‐CoO) are grown on Au(111) and their structural and electronic properties analyzed. The structural quality of the ( 000 1 ¯ ) oriented, oxygen‐terminated, and unreconstructed films allow the application of surface‐science methods to unravel the properties of this unusual polymorph of CoO and may pave the way for future thin‐film applications. An experimental structural analysis by low‐energy electron diffraction (LEED‐IV) is presented with an excellent agreement between measured and calculated intensity spectra expressed by a Pendry R‐factor of R = 0.112 and few‐picometer error bounds in the parameter values. Using scanning tunneling spectroscopy (STS) the bandgap of the semiconducting films is found to be 1.4 ± 0.2 eV. Ultraviolet photoelectron spectroscopy (UPS) confirms the presence of a gap and the position of the Fermi level ( E F ). The structural results of density functional theory calculations using (hybrid) functionals to treat electron correlations and van der Waals forces agree well with the experimentally determined structure of the antiferromagnetic w‐CoO films. In contrast to generalized gradient approximation (GGA)+U calculations, the Heyd–Scuseria–Ernzerhof hybrid functional reproduces the semiconducting nature correctly and predicts surface states in the gap which might pin E F in agreement with STS and UPS. Abstract : Wurtzite cobalt(II) oxide (CoO) is one of the rather elusive polymorphs of cobalt oxide that promises application as sensor material, photocatalyst or photoabsorber. In this study, the growth of epitaxial wurtzite CoO films of high quality is demonstrated. Their structural and electronic properties are determined by application of a multitude of experimental surface‐science methods and density functional theory.